Ionic liquid functionalized synthesis of gold nanoparticles in response to Elaise Guineensis (oil palm) leaves amount - Irfan, M. (American Institute of Physics Inc., 2018)
A modified bio-synthesis method was developed to synthesize gold nanoparticles (AuNPs) using Elaeis Guineensis (oil palm) leaves (OPL) extract prepared in aqueous solution of IL, EMIMOAc. The strong interaction and capping ability of IL at surface of AuNPs was examined through XPS analysis. The effect of OPL powder to liquid (P/L) ratio on absorbance, maximum wavelength (Î»max) and size variation of AuNPs was observed through UV-vis. TEM analysis indicated predominantly spherical shape AuNPs with mean diameter of 15.76 nm. This study exhibits a rapid, cheap and efficient method to achieve stable AuNPs using bio-waste material. Â© 2018 Author(s).